Efektivitas Ekstrak Serai Merah Dan Daun Sirih Merah Sebagai Atraktan Dalam Mengendalikan Hama Lalat Buah (Bactrocera carambolae) Pada Tanaman Cabai - Hara, Astri Kariri; Danga Lewu, Lusia (Prodi Agroteknologi dan Agribisnis - Universitas Kristen Wira Wacana Sumba, 2025)
Chili plants are superior horticultural commodities that are intensively cultivated by farmers. In addition, chili is a staple food for Indonesian people, chili is used as a flavor enhancer in cooking and various other processed food products. This study aims (1) To determine the effect of the effectiveness of red lemongrass and red betel leaf extracts as attractants in controlling fruit fly pests on chili plants, (2) To determine how effective red lemongrass and red betel leaf extracts are as attractants in controlling fruit fly pests at various concentrations. This study was conducted in Lambanapu Village, Kambera District, East Sumba Regency, for 7 days, starting from March 21 to March 28, 2025. This study is an experimental study designed using a factorial randomized block design (RAK), with 2 treatments (RAK Factorial) namely 6 treatments and grouped 3 times so that 18 experimental units were studied, The first factor is the attractant dose consisting of 2 levels as follows: D1 = red lemongrass leaves and D2 = betel leaves. The second factor is the dose of the attractant consisting of 4 levels as follows: P1 = 20%, P2 = 40%, P3 = 60%. The results of the study showed that the use of red lemongrass extract had a significant effect on fruit fly pests in all observed parameters. The use of red betel leaf extract had a significant effect on fruit fly pests. In all observed observation parameters.